Side chain effects in the packing structure and stiffness of redox-responsive ferrocene-containing polymer brushes. (October 2016) - Gan, Lu; Song, Jing; Guo, Shifeng; Jańczewski, Dominik; Nijhuis, Christian A.
Graphical abstract: Highlights: The tether length in redox-active polymer brushes was studied. The tether plays an important role in the supramolecular structure of the brushes. Brushes with short tether are stiff and have well-behaved redox behaviour. Abstract: This paper describes the preparation of ferrocene-containing polymer brushes with different side chain lengths by surface-initiated atom transfer radical polymerization (SI-ATRP). The polymer brushes are characterized by cyclic voltammetry to determine the surface coverage of the ferrocene (Fc) units, their thickness in air by atomic force microscopy (AFM) and ellipsometry, and their mechanical properties by AFM-based nanoindentation. The results are compared against an ideal packing model and we conclude that brushes with short linkers between the Fc units and the polymer back bone are stiff and stand up in air up to 40 nm tall. In contrast, polymers with long linkers collapse and do not stand up in air. Our results indicate that the stiffness and packing structure of Fc-containing polymer brushes are affected by the length of the linkers between the Fc and polymer back bone.